A Simple Fiscal Stress Testing Model Case Studies of Austrian, Czech and German Economies - Kamenik, Ondra (OECD Economics Department Working Papers, 2013)
This paper develops a simple model-based framework for stress testing fiscal consolidation strategies under different scenarios of future shocks. A baseline scenario assuming a gradual debt consolidation is presented and by assuming different future developments (e.g. lower potential growth) and/or model specification in terms of a fiscal rule confidence bands around the baseline are obtained. Trade-offs between costs and benefits are evaluated, in terms of cumulative output loss and primary surpluses, as well as political difficulty of fiscal strategies and risk of failed consolidation. The model is applied to Austria, Czech Republic and Germany. This working paper relates to the 2013 OECD Economic Surveys of Austria, Czech Republic and Germany. (www.oecd.org/eco/surveys)